Analisis Komparatif Bank Digital dengan Bank Semi-Digital - Tutut Dwi Andayani; Dyah Ayu Rizqiana (Jurnal Ekonomi, 2025)
The research is to examine the differences between digital banks and semi-digital banks in order to determine which type of bank is superior, as an evaluation of the implications of adopting a digital banking model as a necessity or merely an option. The research population includes commercial banks listed on the Indonesia Stock Exchange (IDX), with a sample of 6 digital banks and 6 semi-digital banks. Data analysis using STATA version 17 based on financial performance indicators. The results indicate a significant difference based on the indicators of Debt to Asset Ratio, Debt to Equity Ratio, and Net Interest Margin while the Loan to Deposit Ratio, Capital Adequacy Ratio, and Non-Performing Loans didn’t show any financial performance differences between digital banks and semi-digital banks. These findings suggest that adopting a digital banking model is a strategic choice that should be carefully considered and aligned with the available resource capacity.